Kinetically Manipulating the Nucleus Attachment to Create Atypical Defective Rh−Pt Alloyed Nanostructures as Active Electrocatalysts. Issue 20 (21st September 2020) - Liu, Kai; Lyu, Zixi; Chen, Xuejiao; Liao, Xinyan; Chen, Guanhong; Lin, Xin; Wang, Wei; Xie, Shuifen
Abstract: Defective metal nanostructures have attracted great attention due to the striking catalytic behavior of the defect sites. Atypical metal nanocrystals generated from attached nuclei can accommodate abundant grain boundaries (GBs) and twin boundaries (TBs). However, the understanding of their growth‐mechanism and precisely synthetic control over such defective nanocrystals are still scarce. Herein, using the Rh−Pt nanoalloy as a model system, we systematically demonstrate that a prudent control of the reaction kinetics can manipulate the metal nucleation and nucleus attachment to create atypical nanocrystals, including small isolated nanoparticles (NPs), defect‐rich wavy nanowires (WNWs), and {100} facet‐bounded spliced nanocubes (SNCs). In the ethanol oxidation electrocatalysis, the Rh47 Pt53 WNWs featured with abundant TBs and GBs show the greatest mass activity (0.655 A ⋅ mg −1 Pt, 2.9 times to the commercial Pt/C) and durability. Our work captures the core of reaction kinetics on regulating the nucleus attachment and enables the rational control over the nanocrystal morphology and defect. Abstract : A selective synthesis of atypical Rh−Pt alloyed nanocrystals with different morphologies and defective structures has been achieved through kinetically manipulating the nucleation and nucleus attachment. The defective Rh47 Pt53 wavy nanowires endowed with abundant grain boundaries and twin boundaries present a superior electrocatalytic performance for the ethanol oxidation reaction.